Influence of Democratic Leadership on the Performance of Dokkes Personnel at the Indonesian National Police Headquarters: The Mediating Role of Work Discipline - Mawadi, Yusuf; Mashdurohatun, Anis; Wahyunatar, Jaka Kusnanta (KnE Social Sciences, 2025)
A democratic leader is a leader who prioritizes member participation in decision-making and involves them in the planning and implementation process of organizational tasks. Democratic leaders also value the opinions and input of team members, creating an inclusive and collaborative work environment. This study investigates the influence of democratic leadership on the performance of personnel at the Medical and Health Center (DOKKES) of the Indonesian National Police Headquarters, with work discipline as a mediating variable. Using a quantitative approach and structural equation modeling (SEM), the study explores both direct and indirect relationships among variables. Findings reveal that democratic leadership positively impacts both work discipline and performance. Furthermore, work discipline serves as a significant mediator in the relationship between leadership and performance. These results underscore the importance of inclusive leadership and regulatory compliance in improving organizational outcomes within governmental institutions.